GaN HEMT reliability - del Alamo, J.A.; Joh, J. (Microelectronics and reliability, 2009)
This paper reviews the experimental evidence behind a new failure mechanism recently identified in GaN high-electron mobility transistors subject to electrical stress. Under high voltage, it has been found that electrically active defects are generated in the AlGaN barrier or at its surface in the vicinity of the gate edge. These defects reduce the drain current, increase the parasitic resistance and provide a path for excess gate current. There is mounting evidence for the role of the inverse piezoelectric effect in introducing mechanical stress in the AlGaN barrier layer and eventually producing these defects. The key signature of this mechanism is a sudden and non-reversible increase in the gate leakage current of several orders of magnitude. This degradation mechanism is voltage driven and characterized by a critical voltage below which degradation does not occur. This hypothesis suggests several paths to enhance the electrical reliability of GaN HEMTs which are borne out by experiments.